NaLa(MoO4)2: RE3+ (RE3+ = Eu3+, Sm3+, Er3+/Yb3+) microspheres: the synthesis and optical properties. (October 2015) - Gao, Zhiyi; Wang, Zhiying; Fu, Linlin; Yang, Xingxing; Fu, Zuoling; Wu, Zhijian; Jeong, Jung Hyun
Graphical abstract: The strong green upconversion (UC) emission were observed in various Er 3+, Yb 3+ co-doped NaLa(MoO4 )2 samples synthesized via a hydrothermal route. The UC intensity depends on the dopant concentration, and the optimal UC emission was obtained in NaLa(MoO4 )2 : 0.02Er 3+ /0.10 Yb 3+ . Highlights: The NaLa(MoO4 )2 microspheres doped with Eu 3+, Sm 3+ and Er 3+ /Yb 3+ were synthesized by a hydrothermal method. The effects of the EDTA in the initial solution crystal phase and morphology were studied. The down-conversion luminescence properties of NaLa(MoO4 )2 : RE 3+ (RE 3+  = Eu 3+, Sm 3+ ) were investigated. The UC luminescence properties and mechanism of Er 3+ /Yb 3+ co-doped NaLa(MoO4 )2 was discussed. Abstract: NaLa(MoO4 )2 : RE 3+ (RE 3+  = Eu 3+, Sm 3+ ) microspheres have been synthesized at 180 °C via a facile EDTA-mediated hydrothermal route. X-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM), photoluminescence (PL) spectra were employed to characterize the samples. It was found that the amount of EDTA in the initial solution was responsible for crystal phase and shape determination. The effect of Eu 3+ and Sm 3+ doping concentrations on the luminescent intensity was also investigated in details. Furthermore, the up-conversion (UC) emissions have been observed in a series of Er 3+ /Yb 3+ co-doped NaLa(MoO4 )2 samples. Concentration dependent studies revealed that the optimal composition was realized for a 2% Er 3+ and 10% Yb 3+ -doping concentration.